PENGARUH PEMBELAJARAN KONTEKSTUAL TERHADAP KETERAMPILAN MENULIS PUISI KELAS III DI SDN 25 PONTIANAK UTARA - Anggraini, Nur Ria; Halidjah, Siti; Margiati, Margiati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract.The research problem is there is the effect of Contextual Learning on Poetry Writing Skills in Class III of North Pontianak 25 State Elementary School? Aims to analyze how much influence the Contextual Learning on Poetry Writing Skills in Class III of North Pontianak Public Elementary School 25. Using the experimental method with the form of pre-experimental design and design of one group pretest-posttest design. Using a population sample because there is only one class, namely class III which amounts to 31, consisting of 17 daughters and 14 sons. Research instruments used to measure student learning outcomes in the form of poetry writing tests. Data collection techniques in this study are measurement techniques. The study obtained the average pretest was 70.32 and the average post-test was 78.93. Hypothesis test results using t-test obtained t_count = 21.998 for dk = 30 and Î± = 5% obtained t table = 2.042, which means t_count (21.998)> t table (2.042), then Ha is accepted. So, it was concluded that there were differences in student learning outcomes at the pretest and posttest. Effect size (ES) of 0.73 (medium). Thus contextual learning on poetry writing learning has a moderate influence on the learning outcomes of third grade students of North Pontianak 25 State Elementary School.Â Keywords: Influence, Contextual Learning, Poetry.Â